A broad study of two new promising antimycobacterial drugs: Ag(I) and Au(I) complexes with 2-(2-thienyl)benzothiazole - Pereira, Guilherme Alves; Massabni, Antonio Carlos [UNESP]; Castellano, Eduardo Ernesto; Sodre Costa, Luiz Antonio; Fugimura Leite, Clarice Queico [UNESP]; Pavan, Fernando Rogerio [UNESP]; Cuin, Alexandre (Pergamon-Elsevier B.V. Ltd, 2012)
Synthesis, characterization, DFT simulation and biological assays of two new metal complexes of 2-(2-thienyl)benzothiazole - BTT are reported. The complexes [Ag(BTT)(2)NO3] - AgBTT2 and [Au(BTT)Cl]center dot 1/2H(2)O - AuBTT were obtained by mixing the ligand with silver (I) nitrate or gold(I) chloride in methanolic solution. Characterization of the complexes were based on elemental (C, H, N and S), thermal (TG-DTA) analysis, C-13 and H-1 NMR, FT-IR and UV-Vis spectroscopic measurements, as well as the X-ray structure determination for AgBTT2. Spectroscopic data predicted by DFT calculations were in agreement with the experimental data for both complexes. The ligand BTT was synthesized by the condensation of 2-thiophenecarboxaldehyde and 2-aminothiophenol in a microwave furnace. AgBTT2 has a monomeric structure. Both complexes show a good activity against Mycobacterium tuberculosis. Free BIT shows low antitubercular activity. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Benzothiazole; Silver; Gold; Tuberculosis; Mycobacterium